Integument of soft scale insects and the invasion of the pathogenic fungus Lecanicillium lecanii - Xie, Y.; Liu, W.; Xue, J.; Peng, G.; Han, Z.; Zhang, Y. (ENTOMOLOGIA HELLENICA, 2010)
In order to understand how the entomopathogenic fungi infect soft scale insects (Hemiptera: Coccoidea: Coccidae), the integument of four species, namely Ceroplastes japonicus Green, Didesmococcus koreanus Borchsenius, Rhodococcus sariuoni Borchsenius and Coccus hesperidum L. were infected with the pathogenic fungus, Lecanicillium lecanii, strain NO. 3.4504. The invasion process was studied using the electron microscopy and chemical analyses methods. The results showed that the fungal conidia easily become attached on the surface of the cuticle, especially the sites with furrows and ridges. The hyphae penetrate the integument using mechanical force and also by the cuticle degradation by the extracellular enzymes. The fungal penetration results in the structural anamorphosis and disruption of chitin in the procuticle, causing damage and separation of cuticle from the epidermis with wax gland cells. The rise in fungal protease activity occurs prior to the production of chitinase and the activity values correlate with the quantities of the protein and chitin contained in the cuticle of the target scale insects.